Síntese, caracterização e aplicação fotobiológica de 10-{[(piridin-4-il)vinil]fenil}corrol e seus complexos de Pt(II) e Pd(II) - Dozza, Bianca (2022)
The purpose of this work was the synthesis of the free-base corrole 5,15- bis(pentafluorophenyl)-10-{[(pyridin-4-yl)vinyl]phenyl}corrole and its metallic derivatives containing bipyridine complexes of platinum(II) and palladium(II), having as starting materials 5-(pentafluorophenyl)dipyrromethane, 4-[(pyridin-4-yl)vinyl]benzaldehyde, cisdichloro(2,2'-bipyridine)platinum(II) and cis-dichloro (2,2'-bipyridine)palladium(II). The compounds were characterized by elemental analysis (CHN%) and High-Resolution Mass Spectrometry, as well as by electron spectroscopy in the ultraviolet and visible regions, fluorescence emission spectroscopy (steady state and time-resolved) and electrochemistry (cyclic voltammetry). In order to evaluate the photobiological properties of the compounds, aggregation studies in different solvents, photostability measurements, partition coefficient calculations, as well as assays for the generation of reactive oxygen species, such as singlet oxygen and superoxide radical, were also developed. Furthermore, the interaction of the compounds with DNA was investigated experimentally via spectroscopy in the UV-Vis regions and fluorescence emission, and also by viscosimetry, using competing dyes for interaction sites in the biomolecule, such as: acridine orange, ethidium bromide, methyl green and 4',6-diamidino-2-phenylindole. All compounds studied showed good photostability. The free-base corrole H3VpyCor showed a reasonable quantum yield of fluorescence and displays hydrophobic behavior. Possibly, it interacts more effectively in the minor groove of DNA, according to high values of suppression constants (Ksv and kq), and also by theoretical molecular docking calculations. The PtVpyCor derivative showed relevant results in the generation of superoxide radicals, as well as the possibility of interacting with DNA in an intercalative form and through the minor groove. Finally, the PdVpyCor derivative presented the best result in the generation of singlet oxygen, according to values of quantum yield (ΦΔ) and photo-oxidation constant (kfo), and also exhibited the possibility of intercalation with DNA, besides to interaction with the minor groove.